Enhancing Adolescent Health Literacy Through A Community- Based Educational Intervention: A Pilot Study In A Rural Indonesian Setting - M. Bambang Edi Susyanto; Shanti Wardaningsih; Sarah Nur Hidayah (International Journal of Health and Pharmaceutical (IJHP), 2025)
Access to accurate and meaningful health information remains a major challenge for adolescents living in rural areas, which negatively affects their level of health literacy, particularly in relation to general physical health and mental well-being. To address this issue, this preliminary study was designed to examine the extent to which a brief community-based educational intervention could enhance the health literacy capacity of adolescents in rural Indonesia. A total of 33 adolescents aged between 11 and 18 participated in two structured educational sessions, which focused on topics such as nutrition, personal hygiene, emotional regulation, stigma reduction, and peer counseling techniques. Interactive learning activities—including group discussions, scenario-based case problem solving, and role-playing—were employed to strengthen participant engagement and contextualize the material to the local setting. Changes in participants' knowledge were evaluated using a structured questionnaire administered before and after the intervention, covering two main dimensions: general health literacy and mental health literacy. A paired t-test was applied to analyze differences between pretest and posttest scores. The findings revealed a significant improvement in general health literacy, with mean scores increasing from 79.9 (SD = 17.3) to 94.9 (SD = 7.9; p < 0.01). A more substantial improvement was observed in mental health literacy and peer counseling skills, with mean scores rising from 31.82 (SD = 24.43) to 81.82 (SD = 20.98; p < 0.001). Overall, the results indicate that participatory, short-term educational models that are aligned with local cultural values hold considerable promise for strengthening adolescents’ conceptual understanding and emotional engagement with health-related issues, particularly in areas with limited access to healthcare services.